Exploring Endocannabinoid System: Unveiling New Roles in Modulating ER Stress - Ilaria Capolupo; Maria Rosaria Miranda; Simona Musella; Veronica Di Sarno; Michele Manfra; Carmine Ostacolo; Alessia Bertamino; Pietro Campiglia; Tania Ciaglia (Antioxidants)
The endoplasmic reticulum (ER) is the organelle mainly involved in maintaining cellular homeostasis and driving correct protein folding. ER-dependent defects or dysfunctions are associated with the genesis/progression of several pathological conditions, including cancer, inflammation, and neurodegenerative disorders, that are directly or indirectly correlated to a wide set of events collectively named under the term “ER stress”. Despite the recent increase in interest concerning ER activity, further research studies are needed to highlight all the mechanisms responsible for ER failure. In this field, recent discoveries paved the way for the comprehension of the strong interaction between ER stress development and the endocannabinoid system. The activity of the endocannabinoid system is mediated by the activation of cannabinoid receptors (CB), G protein-coupled receptors that induce a decrease in cAMP levels, with downstream anti-inflammatory effects. CB activation drives, in most cases, the recovery of ER homeostasis through the regulation of ER stress hallmarks PERK, ATF6, and IRE1. In this review, we focus on the CB role in modulating ER stress, with particular attention to the cellular processes leading to UPR activation and oxidative stress response extinguishment, and to the mechanisms underlying natural cannabinoids’ modulation of this complex cellular machine.